As vozes (re)veladoras das representações identitárias dos professores universitários do Curso de Letras Inglês - Bastos, Rafael Lira Gomes (2019)
This work, situated in the area of Applied Linguistics, which understands language as a social practice, aims to analyze the dialogical relations of the constitutive social voices in teaching discourse in order to reveal the identity representations of the professors of the English Language Course from Vale do Acaraú State University. Therefore, we organized our theoretical basis from the dialogical conception of language, developed by the Bakhtin Circle (1997, 2006, 2015, 2018), allied to the concepts of social psychology about identity representations (DUVEEN, 2013; MARKOVÁ, 2007, 2017), as a process of discursive (re)construction (MOITA LOPES, 2002, 1998; NORTON, 2016). Our methodological path was guided by the principles of Ergonomics (AMIGUES, 2004; SOUZA-E-SILVA, 2004) and Activity Clinic (CLOT, 2010a, 2010b, 2017; VIEIRA; FAÏTA, 2003), which allowed us the theoretical and methodological support for the teaching activity analysis. We used the simple self-confrontational methodological device with three university professors who volunteered for this research. From the dialogues produced in the simple self-confrontation, we analyzed the dialogical relations between the constitutive social voices of the teaching discourse, the axiological positions of the subjects, their identity representations, in order to recognize the relations of alterity and responsiveness that were allowed to be apprehended through the language activity that emerged from the spatiotemporal displacement made possible by selfconfrontation. The results point to heterogeneous identity representations, strongly marked by the didactic voice and the voice of theorist and methodological knowledge that reveals an English Language professor as interactive and reflective, but who still understands language teaching as an abstract system, facing obstacles of impediment to his action, such as the lack of proficiency of students in the English language and the absence of tools for teaching, thus demonstrating that what is at stake in an analysis of teaching as a professional genre is the real activity that can only be accessed through language.